Proceedings 2019 Workshop on Usable Security 2019
DOI: 10.14722/usec.2019.23025
|View full text |Cite
|
Sign up to set email alerts
|

Work in Progress: On the In-Accuracy and Influence of Android Pattern Strength Meters

Abstract: A common method for helping users select stronger authentication secrets, e. g., passwords, is to deploy a visual strength meter that provides feedback to the user while performing password selection. Recent work considered the accuracy of strength meters for passwords, but there is limited work on understanding the accuracy of strength meters for other knowledge-based authentication types, particularly Android's graphical pattern unlock, despite there being multiple strength meters proposed for patterns in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Andriotis et al [2], Sun et al [24], and Song et al [23] each proposed visual based strength metrics and a display meter to boost diversity of patterns selected. While meters may be an effective means of changing behavior, Golla et al demonstrated that strength metrics used in these meters do not correlate with security, and likely, just the presence of the meter changes behavior [15].…”
Section: Related Workmentioning
confidence: 99%
“…Andriotis et al [2], Sun et al [24], and Song et al [23] each proposed visual based strength metrics and a display meter to boost diversity of patterns selected. While meters may be an effective means of changing behavior, Golla et al demonstrated that strength metrics used in these meters do not correlate with security, and likely, just the presence of the meter changes behavior [15].…”
Section: Related Workmentioning
confidence: 99%
“…To provide more comparison points, we consider a number of other authentication datasets listed in Table I. For example, we use a 3x3 Android unlock pattern dataset described by Golla et al [17], combining four different datasets [6], [27], [39], [45]. It consists of 4637 patterns with 1635 of those being unique.…”
Section: B Datasetsmentioning
confidence: 99%
“…Andriotis et al [3], Sun et al [24], and Song et al [23] each proposed visual based strength metrics and a display meter to boost diversity of patterns selected. While meters may be an e ective means of changing behavior, Golla et al demonstrated that strength metrics used in these meters do not correlate with security, and likely, just the presence of the meter changes behavior [15]. Cho et al proposed SysPal [12], which highlights certain contact points that must be used as part of the pattern, restricting users to select di erent patterns but also more diverse ones.…”
Section: Related Workmentioning
confidence: 99%